Do Financial Deepening, Government Spending, and Unemployment Benefit Poverty Reduction in Indonesia? - Elya Florennica; Ratu Eva Febriani (Department of Development Economics, Universitas Sriwijaya, 2022)
Poverty is classic problem faced in anycountry, various policies are carried out to reduce poverty to prosper the community. This study aims to analyze the effect of financial deepening, government spending, and unemployment on poverty in Indonesia. Observations were made in 33 provinces in Indonesia during the period 2012-2020. The model used is a panel data regression with fixed effect model. The results of this study indicate the financial deepening has a negative and significant effect on poverty, government spending has a negative and significant effect on poverty, and unemployment has a positive and significant effect on poverty. The implication is necessary to increase the role of the financial sector in every province in Indonesia, especially areas that are still low in financial deepening, optimize and increase government spending so that it can create new jobs and reduce the unemployment rate and poverty.